Perspectives on the Structure and Function of the Avian Respiratory System: Functional Efficiency Built on Structural Complexity - Maina, John N. (Frontiers in Animal Science, 2022)
Among the air-breathing vertebrates, regarding respiratory efficiency, the avian respiratory system rests at the evolutionary zenith. Structurally, it is separated into a lung that serves as a gas exchanger and air sacs that mechanically ventilate the lung continuously and unidirectionally in a caudocranial direction. Largely avascular, the air sacs are delicate, transparent, compliant and capacious air-filled spaces that are not meaningfully involved in gas exchange. The avian lungs are deeply and firmly attached to the vertebrae and the ribs on the dorsolateral aspects, rendering them practically rigid and inflexible. The attachment of the lung to the body wall allowed extreme subdivision of the exchange tissue into minuscule and stable terminal respiratory units, the air capillaries. The process generated a large respiratory surface area in small lungs with low volume density of gas exchange tissue. For the respiratory structures, invariably, thin blood-gas barrier, large respiratory surface area and large pulmonary capillary blood volume are the foremost adaptive structural features that confer large total pulmonary morphometric diffusing capacities of O2. At parabronchial level, the construction and the arrangement of the airway- and the vascular components of the avian lung determine the delivery, the presentation and the exposure of inspired air to capillary blood across the blood-gas barrier. In the avian lung, crosscurrent-, countercurrent- and multicapillary serial arterialization systems that stem from the organization of the structural parts of the lung promote gas exchange. The exceptional respiratory efficiency of the avian respiratory system stems from synergy of morphological properties and physiological processes, means by which O2 uptake is optimized and high metabolic states and capacities supported. Given that among the extant animal taxa insects, birds and bats (which accomplished volancy chronologically in that order) possess structurally much different respiratory systems, the avian respiratory system was by no means a prerequisite for evolution of powered flight but was but one of the adaptive solutions to realization of an exceptionally efficient mode of locomotion.